2019
DOI: 10.1155/2019/1818259
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Potential of Portulaca oleracea L. for Parkinson’s Disease Treatment Using a Drosophila Model with dUCH-Knockdown

Abstract: Parkinson’s disease (PD), which is characterized by the decreased motor function and the loss of dopaminergic neurons, is a common neurodegenerative disorder in elders. There have been numerous in vitro and in vivo models developed to study mechanisms of PD and screen potential drug. Recently, dUCH-knockdown Drosophila model has been established and showed potential for screening antioxidants for PD treatment. The dUCH-knockdown Drosophila model of PD mimics most of main PD pathologies such as dopaminergic neu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
14
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 40 publications
3
14
0
1
Order By: Relevance
“…Various metabolic studies have deciphered its phytochemical composition [ 99 , 100 , 102 , 106 ]. Because of its importance in various cultures as an important ethnomedicinal plant, scientists have taken strides to prove its pharmacological potential against various diseases such as diabetes, cancers, neural diseases, asthma, obesity and bacterial and viral diseases using various models including in vivo studies and cell lines [ 24 , 73 , 100 , 180 ]. Main ethnopharmacological properties of purslane are depicted in Figure 4 .…”
Section: Ethnopharmacological Potential Of Purslanementioning
confidence: 99%
See 1 more Smart Citation
“…Various metabolic studies have deciphered its phytochemical composition [ 99 , 100 , 102 , 106 ]. Because of its importance in various cultures as an important ethnomedicinal plant, scientists have taken strides to prove its pharmacological potential against various diseases such as diabetes, cancers, neural diseases, asthma, obesity and bacterial and viral diseases using various models including in vivo studies and cell lines [ 24 , 73 , 100 , 180 ]. Main ethnopharmacological properties of purslane are depicted in Figure 4 .…”
Section: Ethnopharmacological Potential Of Purslanementioning
confidence: 99%
“…Betacyanins from purslane were found to be effective against the D-galactose induced neurotoxicity in mice [29]. Truong et al [180] have found that purslane extract acts as a neuroprotectant against Parkinson's disease because of the presence of levodopa and dopamine. Polysaccharides extracted from Purslane played protective roles against lead induced memory impairment in rats [229].…”
Section: Neuroprotective Potentialmentioning
confidence: 99%
“…Kết hợp với các ưu điểm khác của mô hình như: chi phí thấp, vòng đời ngắn, tốc độ nhân dòng nhanh giúp thu ngắn thời gian và cho phép nghiên cứu trên cỡ mẫu lớn, mô hình ruồi giấm knockdown dUCH phù hợp để sử dụng như một mô hình in vivo sơ cấp trong sàng lọc thuốc điều trị bệnh Parkinson. Tới thời điểm hiện tại, mô hình đã được sử dụng để đánh giá khả năng điều trị Parkinson bằng curcumin, vitamin C, cao chiết rau sam [16][17][18] . Từ những cơ sở trên, chúng tôi tiến hành đánh giá hiệu quả điều trị theo nồng độ của resveratrol đối với bệnh Parkinson trên mô hình ruồi giấm knockdown gene dUCH chuyên biệt tại tế bào thần kinh sinh dopamine.…”
Section: Giới Thiệuunclassified
“…A number of reports exist in the literature on the ethnomedicinal and pharmacological profiles of purslane [4][5][6][7]. Purslane extracts demonstrate various pharmacological activities, such as antioxidant [2,8,9], anti-inflammatory [10][11][12], neuroprotective [13][14][15], antimicrobial [16,17], antidiabetic [18][19][20], antiulcerogenic [21], and anticancer [19,22,23].…”
Section: Introductionmentioning
confidence: 99%